LEGAL PROTECTION FOR CRYPTO ASSETS INVESTMENT IN COMMODITY FUTURES TRADING IN INDONESIA - Daeng Naufal Firjatullah; M. Putra Iqbal (Student Journal of International Law, 2023)
Cryptocurrency/Crypto assets has become increasingly popular when the trading industry was sluggish and chaotic due to the Covid-19 Pandemic. However, there is no adequate regulation by the Badan Pengawas Perdagangan Berjangka Komoditi (Indonesia Bappebti). This article investigates the legal protection of Crypto Assets and Crypto Asset Trading Business Actors, as well as to understand the existence of Crypto Assets as a commodity in Commodity Futures Trading in Indonesia. This study uses normative legal research with a conceptual and statutory approach. The study shows that the Indonesian government, through the Bappebti, has regulated the trading of the Physical Market of Crypto Assets on the Futures Exchange, but there are still inadequate legal protections such as the absence of a Futures Exchange, Futures Clearing House and Crypto Asset Storage Manager. Hence their would be lacked of legal certainty, risk management facilities, and fair competitive pricing. It is recommended to Bappebti to immediately establish a Crypto Futures Exchange, Clearing House and Crypto Asset Storage Manager, along with regulating the use of Expert Advisor and Initial Coin Offerings (ICO).